Circular RNA hsa_circ_0000263 participates in cervical cancer development by regulating target gene of miR‐150‐5p. Issue 7 (19th December 2018) - Cai, Hongning; Zhang, Peng; Xu, Meng; Yan, Lin; Liu, Nian; Wu, Xufeng
Abstract: Circular RNA (circRNA) is a new class of noncoding RNA, and plays an important role in many pathological processes. Cervical cancer is the most common gynecologic malignant tumor. Recently, studies have shown that there is a variety of circRNA involved in the pathogenesis of cervical cancer. We screened out the highly expressed hsa_circ_0000263 from GSE102686 by the quantitative real‐time polymerase chain reaction assay in cervical cancer cell lines. In this study, we investigated whether hsa_circ_0000263 might affect cell proliferation, migration, cell cycle and apoptosis in cervical cancer in vitro and in vivo. The luciferase reporter assay and RNA immunoprecipitation assay confirmed the direct interaction between miR‐150‐5p and hsa_circ_0000263. By using western blot and immunohistochemistry, we confirmed that hsa_circ_0000263 can regulate the expression of murine double minute 4 (MDM4) by affecting miR‐150‐5p, and finally affect the expression of p53 gene. We found that hsa_circ_0000263 was significantly upregulated in cervical cancer cells. In addition, the knockdown of hsa_circ_0000263, would inhibit cell proliferation and migration ability. In conclusion, our current research reveals the important role of hsa_circ_0000263/miR‐150‐5p/MDM4/p53 regulatory network in cervical cancer and provides a new insight into the pathogenesis of cervical cancer. Abstract : Our research team has shown that circ‐0000263 functions as a competitive endogenous RNA to regulate murine double minute 4 (MDM4) expression by sponging miR‐150‐5p is of great significance in the pathogenesis of cervical cancer. And it has suggested that the regulatory axis of circ‐0000263/miR‐150‐5p/MDM4 may play an important role in the pathogenesis and development of cervical cancer by affecting the expression of p53 gene.